Exploring the causal nexus between socio-economic factors, healthcare, and life expectancy in the EU: a panel data analysis - Busu, Mihail; Staicu , Gabriel; Mihaescu-Pintia, Constanța; Copca, Narcis; Skackauskienė, Ilona (Transformations In Business & Economics, 2026)
The present paper analyses the determinants of life expectancy at birth across the European Union (EU) members. Utilising a panel regression analysis based on data from 2015 to 2023, the paper includes socio-economic, demographic, and healthcare factors to estimate their long-run and short-run effects on longevity. The findings illustrate a limited dispersion in life expectancy across the EU countries, while economic and healthcare indicators show considerable heterogeneity. The Granger tests identify bidirectional relationships between life expectancy, fertility rate, and GDP growth. Cointegration analysis confirms a long-run equilibrium relationship between life expectancy and selected factors. The panel least squares estimation highlights the positive influence of health care expenditure and the negative effect of fertility rates on life expectancy, while hospital bed density presents a counterintuitive negative relationship, possibly explained by reverse causality. GDP growth and level of corruption show limited direct long-run effects. The present findings are aimed to provide additional empirical insights for national and EU policymakers to promote more effective health programmes amid economic disparities within the EU.